PENGARUH RASIO LIKUIDITAS DAN RASIO SOLVABILITAS TERHADAP PROFABILITAS PADA PERUSAHAAN MEDIA PERIODE 2019-2022 (YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Khoerunisah, Gusti; Rahmiyatun, Fitri (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to determine the influence of liquidity ratios and solvency ratios on profitability in media companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The samples in this research were 2 media companies using classical analytical research methods and multiple linear analysis. The independent variables used in this research are Current Ratio (X1), Quick Ratio (X2), Debt To Asset Ratio (X3), and Debt to Equity Ratio (X4) while the dependent variable is Return on Assets Ratio (Y). The results of the research show that it is concluded that there is a positive and partially significant influence of the Current Ratio on Return on Assets H01 is accepted and Ha1 is rejected, Quick Ratio has a significant positive effect on Return on Assets H02 is accepted and Ha2 is rejected, Debt to Assets Ratio has a significant positive effect on Return on Assets H03 is accepted and Ha3 is rejected, and the Debt to Equity ratio has a significant positive effect on Return on Assets H04 is accepted and Ha4 is rejected. So there is an influence on liquidity ratios and solvency ratios on media companies listed on the Indonesia Stock Exchange.